THE INFLUENCE OF FAMILY SUPPORTIVE ORGANIZATIONAL CULTURE ON WORK-FAMILY CONFLICT IN WORKING MOTHERS - Liandra Khairunnisa; Hafiz Nurdiansyah (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
The increasing participation of women in the workforce has expanded the role of mothers as individuals responsible not only for their families but also for the demands of their jobs. This condition increases the risk of work-family conflict (WFC), a conflict that arises from a misalignment between the demands of work and family life. This conflict has been identified as a critical issue in industrial and organizational psychology because it affects psychological well-being, job satisfaction, organizational commitment, productivity, and employee turnover intentions. One organizational factor believed to be able to reduce work-family conflict is family supportive organizational culture (FSOC), an organizational culture that supports a balance between work and family through policies, values, norms, and support from leaders and colleagues. This conceptual article aims to examine the relationship between family supportive organizational culture and work-family conflict in working mothers through a synthesis of theories and the results of recent empirical research. The study was conducted using a narrative literature review method by examining various scientific articles published in accredited national journals and reputable international journals in the fields of psychology, organizational behavior, and human resource management. The study results show that a family-friendly organizational culture acts as an organizational resource capable of reducing work-family conflict through work flexibility, supervisor support, coworker support, easy access to family-friendly policies, and reduced stigma against employees who carry out family responsibilities. Based on Conservation of Resources Theory , Role Theory , and Spillover Theory , FSOC contributes to creating a balance between work and family roles so as to improve the psychological well-being of working mothers. This article emphasizes that strengthening a family-friendly organizational culture is an important strategy in supporting work-family balance and sustainable organizational performance and serves as a foundation for future empirical research.